(3MSGf Hf KGHJ GdCfUGQj (B:s (3TGYQ GdfHhI hGdESdGe (B/s - (3YcGhj, QMGH NVQs ((3dHfGf (B- (3HjQhJs (3OGQ GdacQ GdYQHj ,s, 1996)
(3jJfGhd MSGf Hf KGHJ CZQGVg GdTYQjI aj GdLGgdjI GdeOM hGdgLGA GdbHdj hGdTNUj, hcGf efgG GdQKGA hGdMeGSI hGdaNQ hGdZRd, abO XdJ gj YjfgG aj GdGSdGe, Shi Gfg hba eOMg Ydi GdQShd (B((3U(B) (3hbUQ gLGAg Ydi GdeTQcjf hbO GcJSH TYQg aj GdGSdGe cKjQG ef GdGNdGU hGdYPhHI, hcKQJ ajg GdJYGHO GdGSdGejI hGdGbJHGS ef GdbQGf MJi YfO NdjbG HGf jSei QFjS GdHOjYjf agh GdPj HOG af GdTYQ aj GdeOjM GdfHhj(B.s
Keywords: (3MSGf Hf KGHJ Hf GdefPQ GdNRQLj,s -- (3Jhaj (B54 (3gLQjs; (3GdCOH GdYQHjs -- (3JQGLes